Development and reliability of metrics to characterize types and sources of stigma among men who have sex with men and female sex workers in Togo and Burkina Faso - Ashley L. Grosso; Sosthenes C. Ketende; Shauna Stahlman; Odette Ky-Zerbo; Henri Gautier Ouedraogo; Seni Kouanda; Cesaire Samadoulougou; Marcel Lougue; Jules Tchalla; Simplice Anato; Sodji Dometo; Felicity D. Nadedjo; et al. (BMC Infectious Diseases, 2019)
Abstract Background Stigma is a multifaceted concept that potentiates Human Immunodeficiency Virus and sexually transmitted infection acquisition and transmission risks among key populations, including men who have sex with men (MSM) and female sex workers (FSW). Despite extensive stigma literature, limited research has characterized the types and sources of stigma reported by key populations in Sub-Saharan Africa. Methods This study leveraged data collected from 1356 MSM and 1383 FSW in Togo and Burkina Faso, recruited via respondent-driven sampling. Participants completed a survey instrument including stigma items developed through systematic reviews and synthesis of existing metrics. Using exploratory factor analysis with promax oblique rotation, 16 items were retained in a stigma metric for MSM and 20 in an FSW stigma metric. To assess the measures’ convergent validity, their correlations with expected variables were examined through bivariate logistic regression models. Results One factor, experienced stigma, included actions that were carried out by multiple types of perpetrators and included being arrested, verbally harassed, blackmailed, physically abused, tortured, or forced to have sex. Other factors were differentiated by source of stigma including healthcare workers, family and friends, or police. Specifically, stigma from healthcare workers loaded on two factors: experienced healthcare stigma included being denied care, not treated well, or gossiped about by healthcare workers and anticipated healthcare stigma included fear of or avoiding seeking healthcare. Stigma from family and friends included feeling excluded from family gatherings, gossiped about by family, or rejected by friends. Stigma from police included being refused police protection and items related to police confiscation of condoms. The Cronbach’s alpha ranged from 0.71–0.82. Median stigma scores, created for each participant by summing the number of affirmative responses to each stigma item, among MSM were highest in Ouagadougou and among FSW were highest in both Ouagadougou and Bobo-Dioulasso. Validation analyses demonstrated higher stigma was generally significantly associated with suicidal ideation, disclosure of involvement in sex work or same-sex practices, and involvement in organizations for MSM or FSW. Conclusions Taken together, these data suggest promising reliability and validity of metrics for measuring stigma affecting MSM and FSW in multiple urban centers across West Africa.